1994
DOI: 10.1172/jci117081
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I and platelet-derived growth factor-BB induce directed migration of human arterial smooth muscle cells via signaling pathways that are distinct from those of proliferation.

Abstract: Directed migration or chemotaxis of arterial smooth muscle cells (SMC) contributes to intimal SMC accumulation, a key event in the development of atherosclerotic lesions and in restenosis after angioplasty. The present study compares and contrasts insulin-like growth factor I (IGF-I) and platelet-derived growth factor (PDGF-BB) as chemoattractants and mitogens for human arterial SMC. Compared with PDGF-BB, IGF-I is a weaker SMC mitogen. Thus, PDGF-BB, but not IGF-I, evokes a strong and rapid activation of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
281
4
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(304 citation statements)
references
References 51 publications
14
281
4
5
Order By: Relevance
“…The association between PDGF and vascular SMC proliferation has been demonstrated in animal experiments in which the increasing levels of PDGF after arterial injury correlated with neointimal cellular proliferation [45]. Besides stimulating cell growth, PDGF also can induce migration in SMCs, as PDGF is the strongest reported chemoattractant for vascular SMCs [46]. In this study, we found that mechanical injury stimulates PDGF-A expression in SMCs via a MEK/ERK-dependent Egr-1 pathway.…”
Section: Discussionsupporting
confidence: 62%
“…The association between PDGF and vascular SMC proliferation has been demonstrated in animal experiments in which the increasing levels of PDGF after arterial injury correlated with neointimal cellular proliferation [45]. Besides stimulating cell growth, PDGF also can induce migration in SMCs, as PDGF is the strongest reported chemoattractant for vascular SMCs [46]. In this study, we found that mechanical injury stimulates PDGF-A expression in SMCs via a MEK/ERK-dependent Egr-1 pathway.…”
Section: Discussionsupporting
confidence: 62%
“…However, it is possible that other growth factors or adhesion receptors are signaling via PLCg (Carpenter and Ji, 1999;Jones et al, 2005). As PLCg seems to serve as a point of convergence for PDGF, HGF and IGF-1 in addition to EGF in signaling motility (Bornfeldt et al, 1994;Kundra et al, 1994), expression of PLCz would be expected to diminish cell motility signaled by all of these factors. Furthermore, PLCg has been linked to integrin-related changes that result in cell motility in the context of invading cancer cells (Jones et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The signal transduction pathways that are activated in response to IGF-1 were determined. We studied the two most well known, distinct downstream pathways of IGF-1 namely the PI3K and the MAPK pathway (Bornfeldt et al, 1994;Puglianiello et al, 2000;Tu et al, 2000;Qiang et al, 2002). The 5TMM model was used since this is an ideal in vivo model for testing different inhibitors of IGF-1.…”
mentioning
confidence: 99%